2021
DOI: 10.3389/fmicb.2021.714371
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antibiofilm Activities of Chloroindoles Against Vibrio parahaemolyticus

Abstract: Vibrio parahaemolyticus is a food-borne pathogen recognized as the prominent cause of seafood-borne gastroenteritis globally, necessitating novel therapeutic strategies. This study examined the antimicrobial and antivirulence properties of indole and 16 halogenated indoles on V. parahaemolyticus. Among them, 4-chloroindole, 7-chloroindole, 4-iodoindole, and 7-iodoindole effectively inhibited planktonic cell growth, biofilm formation, bacterial motility, fimbrial activity, hydrophobicity, protease activity, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 50 publications
3
28
0
Order By: Relevance
“…Several indole derivatives have been shown to exhibit antibiofilm activity against various microbes, for example, 3-indolylacetonitrile against enterohemorrhagic E. coli O157:H7 (14), methylindoles ( 18 ) or 7‐benzyloxyindole ( 27 ) against C. albicans , iodoindoles against A. baumannii ( 19 ), several halogenated indoles derivatives against S. marcescens ( 20 ), and chloroindoles against V. parahaemolyticus ( 21 ). Unlike other indoles in previous studies, in this study, DIM and indole-3-carbinol both efficiently inhibited biofilm formation by C. acnes .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several indole derivatives have been shown to exhibit antibiofilm activity against various microbes, for example, 3-indolylacetonitrile against enterohemorrhagic E. coli O157:H7 (14), methylindoles ( 18 ) or 7‐benzyloxyindole ( 27 ) against C. albicans , iodoindoles against A. baumannii ( 19 ), several halogenated indoles derivatives against S. marcescens ( 20 ), and chloroindoles against V. parahaemolyticus ( 21 ). Unlike other indoles in previous studies, in this study, DIM and indole-3-carbinol both efficiently inhibited biofilm formation by C. acnes .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, indole controls quorum sensing and biofilm formation of its own species and in other bacterial species ( 12 ). However, several indole derivatives have more potent antimicrobial and antibiofilm activities than indole such as 3-indolylacetonitrile, 7-hydroxyindole, 7-benzyloxyindole, methylindoles, iodoindoles, fluoroindoles, chloroindoles against Escherichia coli ( 14 , 15 ), Pseudomonas aeruginosa ( 15 ), Paenibacillus alvei ( 16 ), S. aureus ( 17 ), C. albicans ( 18 ), Acinetobacter baumannii ( 19 ), Serratia marcescens ( 20 ), Vibrio parahaemolyticus ( 21 ), and others.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, some antibiotics can affect bacterial virulence in addition to their growth inhibition ability. For instance, it was reported that linezolid could diminish the virulence factors’ production from S. aureus [ 50 , 51 ]. Thus, we also explored the anti-biofilm activity of SOTE by crystal violet assay and qRT-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial compounds are usually more effective when they also have anti-biofilm activity. They will be able to penetrate the formed biofilms, exert their antibacterial activity, and diminish biofilm formation [ 51 ]. SOTE decreased the percentage of E. faecalis isolates strongly and moderately, forming biofilm from 60.87% to 21.74%.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several indole analogues have been reported to reduce bacterial virulence. For example, 4-iodoindole, 7-iodoindole, 4-chloroindole, and 7-chloroindole were found to effectively inhibit biofilm formation, bacterial motility, fimbrial activity, hydrophobicity, protease activity, and indole production in Vibrio parahaemolyticus ( 29 ). Furthermore, 7-fluoroindole ( 30 ), 7-hydroxyindole ( 31 ), and 3-indolylacetonitrile ( 32 ) reduced the production of virulence factors in Pseudomonas aeruginosa .…”
Section: Introductionmentioning
confidence: 99%